Effect of Azithromycin plus Rifampin versus That of Azithromycin Alone on the Eradication of Chlamydia pneumoniae from Lung Tissue in Experimental Pneumonitis - Wolf, Katerina (American Society for Microbiology, 1999)
Azithromycin, doxycycline, and rifampin, alone or in combination, were tested in vitro against Chlamydia pneumoniae AR-39. The combination of azithromycin plus rifampin showed the strongest activity and produced higher rates of eradication of C. pneumoniae from lung tissues than azithromycin alone in experimental mouse pneumonitis.